Automatic Fish Feed Design and IoT Based Monitoring Using NodeMCU ESP8266 Microcontroller - Sobri, Muhammad Ali; Topiq, Salman (Journal Corner of Education, Linguistics, and Literature, 2024)
Fish farming in Pasaman Regency is growing rapidly, but still faces the challenge of uncontrolled feeding, which increases production costs and reduces water quality. This study develops an IoT-based automatic feeding system with NodeMCU ESP8266 to precisely set the schedule and amount of feeding, monitor water conditions in real-time, and enable remote control via smartphone. As a result, this system increases efficiency, reduces operational costs, and supports the sustainability of fish farming, so it is expected to be a model for the development of aquaculture in Indonesia. Aquaculture plays a significant role in food production, and efficient fish feeding is essential for optimal growth and resource management. Traditional feeding methods often lead to overfeeding, underfeeding, and inconsistent feeding schedules, affecting fish health and increasing operational costs. This study proposes the design and implementation of an automatic fish feeder integrated with an IoT-based monitoring system using the NodeMCU ESP8266 microcontroller. The system enables precise control over feeding times and portions, reducing feed waste and ensuring better fish nutrition. Real-time monitoring is achieved through IoT connectivity, allowing users to track feeding activities and environmental conditions remotely via a mobile application or web interface. The research focuses on system design, hardware development, software implementation, and performance evaluation. The results demonstrate the system's effectiveness in optimizing fish feeding, enhancing aquaculture efficiency, and providing a user-friendly monitoring solution. This innovation contributes to smart aquaculture practices, promoting sustainability and cost-effective fish farming.